Pengaruh Kompensasi Dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan PT Astra Daihatsu Metro - Komalia, Komalia; Riyanto, Kuncoro Budi (Jurnal Manajemen DIVERSIFIKASI, 2022)
This study aims to determine the effect of compensation and work motivation on employee productivity. The type of research conducted in this research is using quantitative research. Data collection is done by giving questionnaires to employees of PT. Daihatsu Metro City, amounting to 121 people as research respondents. The data analysis technique used is multiple linear regression. The results of the study show that compensation has a positive and significant effect on work productivity. The results of this study are supported and in line with research conducted by Gofur (2019) which shows that compensation has a positive and significant effect on work productivity. Self-motivation has a positive and significant influence on work productivity. This shows that if employees' perceptions of self- motivation will be fulfilled according to the wishes of employees, it will affect work productivity. Compensation and work motivation together have a positive and significant effect on work productivity